Preliminary Study on Willingness to Pay for Adaptive Management in Komodo National Park: A Contingent Valuation Approach - Dendra, Syahda Hati; Sianipar, Imelda Juniaty; Rahman, Ari; Sofiyah, Evi Siti; Suhardono, Sapta; Suryawan, I Wayan Koko (Institut Teknologi Sepuluh Nopember, 2024)
Komodo National Park (KNP), a UNESCO World Heritage Site, faces significant environmental challenges due to increasing tourism, climate change, and resource management issues. This preliminary study employs the Contingent Valuation Method (CVM) to estimate visitors' willingness to pay (WTP) for adaptive management initiatives aimed at preserving the park's unique biodiversity and ecological health. Conducted in Labuan Bajo, the main gateway to KNP, the study involved 50 respondents who were surveyed on their WTP for improved environmental quality and management. The binary logistic regression analysis revealed that higher income levels and gender significantly influence WTP, with higher income individuals and males being more likely to contribute financially. Marital status showed a negative association with WTP, suggesting that married individuals may have financial constraints. The study highlights the importance of understanding sociodemographic factors to design effective funding strategies for conservation. The findings underscore the need for targeted communication and engagement strategies to increase financial support for adaptive management. These insights will inform policy and management strategies to ensure the long-term sustainability of KNP.